(untitled) (Bangladesh Journal of Pharmacology, 2016)
It was aimed to explore the expression level of miRNA-486 and miRNA-499 in the plasma of lung cancer patients and analysis their differences in expre-ssion. The expression level of both miRNA-486 and miRNA-499 in the plasma of non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) were lower than that of the control group (p<0.05) and the decrease was more obvious in NSCLC. Compare with the miRNA-499?expression quantity in NSCLC patients plasma. There was statistical significance difference (p<0.05) between III??stage and I?II stage. The expression quantity of miRNA in plasma of patients with extensive-stage SCLC was lower than that of patients with limited-stage SCLC (p<0.05). The sensitivity and specificity of plasms miRNA-486 respectively were 88.5% and 83.3%. The expression of miRNA-499 and miRNA-486 in lung cancer patients were up-regulated, and might be closely related to the occurrence and prognosis of lung cancer, and might be used as potential screening and prognosis index for lung cancer.